Analisis Frequency Rate dan Severity Rate dalam Kecelakaan Kerja di PT Konstruksi Listrik Rzq - Harahap, Rizqiyani Khoiriyah; Jannah, Farahul (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The occupational safety and health (K3) program is one of the important parts that needs to be implemented in the implementation of work.that needs to be implemented in the implementation of work. The risk of accidents and occupational diseasesdue to work often occur because the company does not implement the K3 program properly.program properly. This can have an impact on the level of worker productivity. WithThe implementation of the OHS program is expected to increase employee productivity.employees. To find out how the implementation of the K3 program affectswork productivity and how big the relationship between the two is thenresearch was conducted on employees at PT RZQ Electrical Construction. This study aims to analyze the frequency rate and severity rate in work accidents at PT RZQ Electrical Construction. Occupational safety is related to machines, work tools, and their processing, workplace and environmental foundations and ways of doing work. KeyWords: Occupational Safety And Health, Frequency Rate, Severity Rate, Work Accident  ABSTRAK Program keselamatan dan kesehatan kerja (K3) merupakan salah satu bagian penting yang perlu diterapkan dalam pelaksanaan kerja. Risiko kecelakaan serta penyakit akibat kerja sering terjadi karena pihak perusahaan tidak menerapkan program K3 dengan baik. Hal ini dapat berdampak pada tingkat produktivitas pekerja. Dengan adanya implementasi program K3 diharapkan dapat meningkatkan produktivitas kerja karyawan. Untuk mengetahui bagaimana pengaruh implementasi program K3 terhadap produktivitas kerja serta seberapa besar hubungan antara keduanya maka dilakukanlah penelitian terhadap karyawan pada PT Konstruksi Listrik RZQ. Penelitian ini bertujuan untuk menganalisis frequency rate dan severity rate dalam kecelakaan kerja di PT konstruksi listrik RZQ. Keselamatan kerja berkaitan dengan mesin, alat kerja, dan proses pengolahannya, landasan tempat kerja dan lingkungan serta cara-cara melakukan pekerjaan. Kata Kunci: Keselamatan Dan Kesehatan Kerja, Frequency Rate, Severity Rate, Kecelakaan Kerja